2004
DOI: 10.1002/j.2333-8504.2004.tb01940.x
|View full text |Cite
|
Sign up to set email alerts
|

Accommodations on High‐stakes Writing Tests for Students With Disabilities

Abstract: With the addition of a writing component to many high-stakes tests (e.g., college admission tests and high school exit exams), a review of writing accommodations for students with disabilities becomes critical. This paper reviews the accommodation policies of 20 states with high school exit exams of writing and three testing organizations that administer high-stakes tests that assess writing. In addition, this paper reviews existing research on testing accommodations, specifically those that focus on writing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Several studies have compared the difference between the quality scores of handwritten and word-processed essays for students with and without disabilities (Arnold et al, 1990;Cahalan-Laitusis, 2003;Hollenbeck, Tindal, Stieber, & Harniss, 1999;Powers, Fowles, Farnum, & Ramsey, 1994;Russell & Plati, 2001). Consistently, research results have indicated that student papers that are converted to word-processed versions receive lower scores than do the original handwritten versions.…”
Section: Handwriting Biasmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have compared the difference between the quality scores of handwritten and word-processed essays for students with and without disabilities (Arnold et al, 1990;Cahalan-Laitusis, 2003;Hollenbeck, Tindal, Stieber, & Harniss, 1999;Powers, Fowles, Farnum, & Ramsey, 1994;Russell & Plati, 2001). Consistently, research results have indicated that student papers that are converted to word-processed versions receive lower scores than do the original handwritten versions.…”
Section: Handwriting Biasmentioning
confidence: 99%
“…For an adolescent with written expression deficits, this essay requirement often presents a significant barrier to graduation from high school, entry into and exit from postsecondary institutions (technical schools, universities), acceptance into professions (licensure), and success on the job. Although many professionals consider timed impromptu essays formulaic and unresponsive to the process of writing, the fact remains that such tasks are often levers of success for students (Cahalan-Laitusis, 2003;White, 1995). In fact, today even most portfolio writing assessments include one or more impromptu essays.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of word processing as a test response accommodation for adolescents and/or adults with LD or ADHD has been inconclusive (Cahalan-Laitusis, 2003). Researchers reporting no differences in scores between word processed and handwritten versions of timed essay writing reviewed studies conducted a decade or more ago (Hollenbeck, Tindal, Harniss, & Almond, 1999; MacArthur & Graham, 1987).…”
Section: Test Accommodations— Findings From the Literaturementioning
confidence: 99%